(3JhVjM GdeTJHgs - (3eMeO Hf YHO Gddg (B((3CHj HcQ(B) (3Hf eMeO GHf CMeO Hf eLGgO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf , (B842 (3g` s; (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s ((3EHQGgje Hf eMeO Hf eMehO Hf HOQ GdMfHdi s)
(3ChdgG (B:s
(3GdMeO ddg TQM ddeJbjf HJhVjM GdeTJHg UOhQkG EdN s
(3BNQgG (B:s
(3jfJgi Edi BNQ HGSe (B: (3GdNjhGfi s
(3LGA HBNQ GdLRA GdChd(B:(3BNQ GdeLdO GdJGSY YTQ HYO GdeGFI ef GdchGcH GdOQGQi hai BNQ GdLRA GdKGfi BNQ GdeLdO GdYTQjf HYO GdeGFI gi GdchGcH GdOQGQi hcJHgG eMeO Hf HOQ GdMfHdi SfI (B830(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B46 s
Keywords: (3GdJGQjNs